2017
DOI: 10.18632/oncotarget.23199
|View full text |Cite
|
Sign up to set email alerts
|

CCAR2 negatively regulates IL-8 production in cervical cancer cells

Abstract: Cell cycle and apoptosis regulator 2 (CCAR2) is a multifaceted protein that controls diverse cellular functions; however, its function in cancer is unclear. To better understand its potential role in cancer, we examined gene expression patterns regulated by CCAR2 in cervical cancer cells. Cytokine and chemokine production by CCAR2-deficient cells increased under oxidative conditions. In particular, H2O2-treated CCAR2-depleted cells showed a significant increase in interleukin-8 (IL-8) production, indicating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We show herein that CCAR2 co-immunoprecipitates with ESRP1 in HCA24 cells, but its expression was not regulated by ESRP1 level in the different CRC cell lines used in the present study. CCAR2, found on human chromosome 8 (8p21.3), is involved in multiple cellular processes, and like ESRP1, it has a dual role in cancer depending on the context [33]. Importantly, CCAR2 is a core component of the DBIRD complex, a multiprotein complex, which acts at the interface between core messenger RNP particles and RNA polymerase II, and integrates transcript elongation with regulation of alternative splicing [34].…”
Section: Discussionmentioning
confidence: 99%
“…We show herein that CCAR2 co-immunoprecipitates with ESRP1 in HCA24 cells, but its expression was not regulated by ESRP1 level in the different CRC cell lines used in the present study. CCAR2, found on human chromosome 8 (8p21.3), is involved in multiple cellular processes, and like ESRP1, it has a dual role in cancer depending on the context [33]. Importantly, CCAR2 is a core component of the DBIRD complex, a multiprotein complex, which acts at the interface between core messenger RNP particles and RNA polymerase II, and integrates transcript elongation with regulation of alternative splicing [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that elevated production of IL-8 triggered by cell cycle and apoptosis regulator 2 under conditions of oxidative stress has a role in inflammation and progression of CC. 52 IL-12 is a heterodimeric pro-inflammatory cytokine with antitumor activity because it promotes cytotoxic T cell (CTL) responses and Th1 adaptive immunity. The polymorphisms in the IL12 gene, IL12Brs3212227 and IL12Ars568408 contribute to the risk of CC.…”
Section: Inflammation and CCmentioning
confidence: 99%
“…In addition to IL‐10, IL‐8 plays a causative role in acute inflammation. It has been suggested that elevated production of IL‐8 triggered by cell cycle and apoptosis regulator 2 under conditions of oxidative stress has a role in inflammation and progression of CC . IL‐12 is a heterodimeric pro‐inflammatory cytokine with antitumor activity because it promotes cytotoxic T cell (CTL) responses and Th1 adaptive immunity.…”
Section: Inflammation and CCmentioning
confidence: 99%
“…In CCAR2-deficient cells, the expression of IL-8 is upregulated by activating the transcription factor AP-1. This is also related to a shorter survival of CC patients [16]. Most somatic mutations that occur in a cell are biologically neutral, which means they will not trigger cancer progression.…”
Section: Cytokines: a Cause Of Inflammation In Hpv-mediated CCmentioning
confidence: 99%